186k views
0 votes
Simplify this expression.

2\sqrt5(13+\sqrt2)

2 Answers

6 votes

Explanation:

everything can be found in the picture

Simplify this expression. 2\sqrt5(13+\sqrt2)-example-1
User Karthi R
by
6.0k points
2 votes

Answer:


\small{\boxed{\tt{2 √(5) (13 + √(2) = 26 √(5) + 2 √(10) = 64.3}}}

Explanation:

Given : Expression


2 √(5) (13 + √(2) )

To find : Simplify the expression

Solution :

Step 1 - Write the expression


2 √(5) (13 + √(2) )

Step 2 - Apply distributive property,


a(b + c) = a × b + a * c


= 2 √(5) * 13 + 2 √(5 ) * √(2)

Step 3 - Apply square root property,


√(x) * √(y) = √(xy)


= 26 √(5) + 2 √(10)

or to simplify more substitute the value of
√(5) = 2.23 and
√(10) = 3.16

Simplification-


= 26(2.23) + 2(3.16)


= 57.98 + 6.32


= 64.3

User Nirmit Dagly
by
5.9k points